FACTORS RELATED TO BURNOUT INCIDENCE IN MIDWIVES DURING THE COVID-19 PANDEMIC - Helda Sevya Islamiyah; Nining Febriyana; Ratna Dwi Jayanti (Indonesian Midwifery and Health Sciences Journal, 2023)
Background: Health workers including midwives have the potential to experience mental fatigue or burnout syndrome caused by prolonged stress to interpersonal pressure, especially at work. The COVID-19 pandemic has caused an increase in the burden of health services which can also increase the incidence of burnout. During the COVID-19 pandemic, the percentage of midwives who experienced burnout was 83%. Burnout in midwives can have an impact on reducing the quality of health services. The purpose of this study was to analyze the factors associated with the incidence of burnout among midwives during the COVID-19 pandemic at Dr. Soetomo City of Surabaya. Method: This study uses an analytic observational method with a cross-sectional approach which aims to correlate the burnout variable in midwives with the variables age, length of work, marital status, relationship with husband/family, husband/family support, number of children, and personality. Total population of 94 midwives with the sampling technique using total sampling. The instrument used is a questionnaire. The collected data were analyzed using chi-square analysis. Results: out of 94 midwives, 53 midwives were included in the inclusion. A total of 36 midwives (68%) experienced moderate burnout, 9 midwives (17%) experienced severe burnout, and 8 midwives (15%) experienced mild burnout. Based on this study, factors related to burnout are age and length of service, while factors that are not related are marital status, relationship with husband/family, family support, number of children, and personality. Conclusion: The data shows that most of the midwives who participated in the study experienced burnout in the moderate category related to the age and length of work of the midwives. Keywords : burnout in midwives, pandemic COVID-19, related factors